Skin Sensitization Testing Using New Approach Methodologies - Judy Strickland (Toxics)
Chemical regulatory authorities require skin sensitization information for a number of chemical sectors, such as cosmetics, pesticides, newly marketed chemicals, household products, and topical pharmaceuticals [...]